“How Do You Knit Together Two Parts of a Single Life Lived Decades Apart?”: Reentry Planning of Juvenile Lifers - Taylor, Melanie (American journal of criminal justice, 2024)
Those sentenced to life in prison without the possibility of parole as juveniles were recently granted opportunities for release when the Supreme Court ruled that they must be retroactively reprocessed. This is a population that was never expected to be released from prison, resulting in minimal reentry programming and treatment. Now that many are preparing for release it is unclear if they are ready to reenter their communities. In the current study, 123 juvenile lifers discussed their preparation for reentry and expectations for release. Findings indicate that they plan to depend largely upon family and spouses for support; that they are attempting to prepare themselves for entry in a variety of ways, but many have been prevented from programming; and most have modest career and educational goals, but some have ambitious plans for release. This study is an important first step in understanding how juvenile lifers will reenter their communities.